Examining the impact of Culture's consequences: A three-decade, multilevel, meta-analytic review of Hofstede's cultural value dimensions. - Taras, Vas; Kirkman, Bradley L.; Steel, Piers (Journal of Applied Psychology, 2010)
Using data from 598 studies representing over 200,000 individuals, we meta-analyzed the relationship between G. Hofstede's (1980a) original 4 cultural value dimensions and a variety of organizationally relevant outcomes. First, values predict outcomes with similar strength (with an overall absolute weighted effect size of rho = 0.18) at the individual level of analysis. Second, the predictive power of the cultural values was significantly lower than that of personality traits and demographics for certain outcomes (e.g., job performance, absenteeism, turnover) but was significantly higher for others (e.g., organizational commitment, identification, citizenship behavior, team-related attitudes, feedback seeking). Third, cultural values were most strongly related to emotions, followed by attitudes, then behaviors, and finally job performance. Fourth, cultural values were more strongly related to outcomes for managers (rather than students) and for older, male, and more educated respondents. Fifth, findings were stronger for primary, rather than secondary, data. Finally, we provide support for M. Gelfand, L. H. Nishii, and J. L. Raver's (2006) conceptualization of societal tightness-looseness, finding significantly stronger effects in culturally tighter, rather than looser, countries.